Exploring the association between social isolation and utilization of primary health services by older adults: evidence from China - Xie, Xinlong; Lyu, Yanxia; Li, Xinyu; Zhuang, Zhiruo; Xu, Aijun (Frontiers in Public Health, 2024)
Objective: This study aims to investigate the impact of social isolation on the utilization of primary health services among older adults in China. Methods: Data from the China Longitudinal Aging Social Survey (CLASS) conducted in 2018 were utilized. A binary logistic regression model was established, and propensity score matching (PSM) was employed for analysis. Results: The results of the binary logistic regression showed that family isolation within social isolation had a significant negative impact on the utilization of primary health services for older adults. In contrast, there was no significant association between friend isolation, community isolation, and the utilization of primary health services. Furthermore, the PSM results, using three matching methods (nearest neighbor matching, radius matching, and kernel matching), confirmed that family isolation significantly reduced older adults’ utilization of primary health services, , consistent with the baseline regression findings. Conclusion: Reducing the occurrence of family isolation among older adults may be a cost-effective intervention measure. Efforts should be directed toward improving family support for older adults, promoting the utilization of primary health services, and strengthening disease prevention.